JNK/c-Jun cascade activation enhances malignant proliferation of psoriatic keratinocytes by regulating ROS levels and mitochondrial membrane potential - Yu Zhang; Anqi Yin; Nannan Tong; Yadong Xue; Yuzhen Li (European Journal of Medical Research)
Abstract Psoriasis is a chronic immune-mediated skin disorder characterized by excessive keratinocyte proliferation, inflammation, and oxidative stress. This study investigates the role of the JNK/c-Jun cascade in psoriasis pathogenesis, focusing on its impact on keratinocyte proliferation and inflammatory responses. An in vitro psoriasis model was established using M5-stimulated HaCaT keratinocytes, while an in vivo model was created with imiquimod-treated Wistar rats. The results indicated that M5 stimulation significantly enhanced keratinocyte viability and proliferation, as demonstrated by increased optical density, EdU incorporation, and Ki-67 expression. M5 treatment also elevated pro-inflammatory cytokines TNF-α, IL-1β, and IL-6, while inducing oxidative stress through increased ROS production, lipid peroxidation, and mitochondrial membrane potential (MMP) disruption. Blocking the JNK/c-Jun cascade with the SP600125 inhibitor effectively reduced keratinocyte hyperproliferation, cytokine secretion, and oxidative stress, while restoring mitochondrial integrity. In addition, knockdown of Nrf2 suppressed M5-induced ROS generation, inflammatory signaling, and antioxidant enzyme activity. In psoriasis rats, JNK/c-Jun inhibition significantly alleviated skin tissue damage, reducing inflammatory cell infiltration, epidermal hyperkeratosis, and phosphorylation of key inflammatory markers. Correspondingly, serum pro-inflammatory cytokines were decreased, and oxidative stress indices improved. These findings suggest that the JNK/c-Jun cascade plays a central role in psoriasis pathogenesis by regulating keratinocyte proliferation, inflammation, and oxidative stress. Targeting this pathway presents a promising therapeutic strategy for psoriasis treatment. Further studies are warranted to explore upstream regulators and downstream effectors of the JNK/c-Jun signaling pathway.